Pengaruh Karakteristik Inovasi Terhadap Niat Mengadopsi Solopos Epaper - Sholahuddin, Sholahuddin, Dr. Anton Agus Setyawan, M.Si, Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2017)
This paper to examines factors that the influence of innovation characteristic to intention to adopt Solopos epaper. Nowdays, many newspaper companies in Indonesia to offer the electronic paper (epaper) services. But not many studies that analyze the factors that might help the industry of epaper for designing epaper services. This research will to fill the lack of studies on the epaper phenomena. This study investigated the factors that influence the intention to adopt Solopos epaper. Using the Diffusion of Innovations and Technology Acceptance Model (TAM) as the baseline theory, this research involved 103 respondents from Solopos readers. Research shows that relative advantage and observability have positive impact to intention to adopt Solopos epaper. And then, compatibility, complexity, and trialability don't have positive impact to intention to adopt Solopos epaper. The result of this research is usefull for developing electronic newspaper industry in Indonesia.